PENGARUH MOTIVASI DAN STRESS KERJA TERHADAP KINERJA KARYAWAN SELAMA PANDEMI COVID-19 PT SINAR CENDANA KOTA BATAM - Friskilla, Intan; M. Khoiri (SCIENTIA JOURNAL, 2022)
This study aims to determine the effect of motivation and work stress on employee performance during the covid-19 pandemic at PT. Sinar Cendana Batam City. Employees are the main factor to determine whether a company fails or succeeds in achieving its planned goals. Therefore, the performance of each employee needs to be considered by each leader, because reduced employee performance will have an impact on company performance. This type of research is quantity with a population of employees of PT. Sinar Cendana Batam City as many as 100 respondents. Statements are given using a questionnaire with census techniques, with data analysis techniques Classical assumption test and hypothesis testing. The results showed that work motivation had a positive and significant effect on employee performance, job stress had a positive and significant effect on employee performance. So it can be concluded that between the two variables studied, it has a positive and significant effect on employee performance